KEANEKARAGAMAN JENIS VEGETASI TINGKAT POHON DI HUTAN ADAT GUNUNG SOKA DUSUN PADANG SEBATIK KECAMATAN AIR BESAR KABUPATEN LANDAK - Tarsius, .; Hardiansyah, Gusti (JURNAL HUTAN LESTARI, 2019)
Forest is an ecosystem unit in the form of a stretch of land containing biological natural resourcesdominated by trees in its natural environment which can not be separated from the life of indigineous communities. This study aims to find out the diversity of vegetation types of stand composition trees in Gunung Soka Indigenous Forest. This study used transect method and the transect lineswere determined purposively. There were 4 (four) transect lines with 500 m lenght, 10 m wide to the left and 10 m wide to the right. The observation plot was 20 m, and there were 25 plots, so the total was 1 ha. There were 100 plots to study with 4 transect line so the total area was 4 ha. The result show that there are 23 trees vegetation consists of 13 family, 741 of individual trees in Gunung Soka Indigenous Forest. The highest important value index (INP) was found in engkabang bukit (Shorea pinanga Scheff.) with a value of 82,25, while the lowest important value index was found in keraci (Quercus lucida Roxb.) with a value of 1,42. The Dominance index (C) of trees vegetation is 0,17525 or C = 1 ,which shows that there are more than one dominant tree. The Diversity index (DS) of trees vegetation is closte to 1, which shows moderate diversity of species. The Highest species Abundance index (e) of tree vegetation was found in line 1 with a value of 0,9493, meanwhile the lowest value was found in line 2 with a value of 0,5764.Kata Kunci : Diversity,indigenous forest, tree vegetation